2015
DOI: 10.1161/circimaging.115.003642
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sensitive Cardiac Magnetic Resonance Imaging for Prediction of Ventricular Arrhythmia Risk in Patients With Chronic Myocardial Infarction

Abstract: BACKGROUND Recent canines studies have shown that iron deposition within chronic myocardial infarction (CMI) influences the electrical behavior of the heart. To date, the link between the iron deposition and malignant ventricular arrhythmias (mVA) in humans with CMI is unknown. METHODS AND RESULTS CMI patients (n=94) who underwent late-gadolinium-enhanced CMR prior to ICD implantation for primary and secondary prevention were retrospectively analyzed. The predictive values of hypointense cores (HIC) in balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
1
11
0
2
Order By: Relevance
“…Furthermore, residual myocardial iron as a consequence of intramyocardial hemorrhage has also been shown to be pro-arrhythmic. 105 Although all these were relatively small and single-center studies, CMR has shown promise to improve the risk-stratification of STEMI patients at risk of ventricular arrhythmias. With the availability of inline, automated ECV-mapping 106 and free-breathing T2*-mapping 93 , characterization of the infarct size and peri-infarct zone and infarct core may become more objective and CMR would play an invaluable role to identify those most likely to benefit from a primary prevention ICD in a near future.…”
Section: Future Directionsmentioning
confidence: 99%
“…Furthermore, residual myocardial iron as a consequence of intramyocardial hemorrhage has also been shown to be pro-arrhythmic. 105 Although all these were relatively small and single-center studies, CMR has shown promise to improve the risk-stratification of STEMI patients at risk of ventricular arrhythmias. With the availability of inline, automated ECV-mapping 106 and free-breathing T2*-mapping 93 , characterization of the infarct size and peri-infarct zone and infarct core may become more objective and CMR would play an invaluable role to identify those most likely to benefit from a primary prevention ICD in a near future.…”
Section: Future Directionsmentioning
confidence: 99%
“…43 In patients with chronic ischemic cardiomyopathy who subsequently received an ICD, early evidence suggests that iron may be a strong predictor of ventricular arrhythmias with a 33-fold increase in odds for a significant arrhythmic event. 44 CMR has revealed hemorrhagic infarction and chronic iron deposition as potentially new physiological mechanisms of heart failure and arrhythmia in CAD.…”
Section: Noncontrast Parametric Mapping Techniquesmentioning
confidence: 99%
“…[1][2][3] HTN induces myocardial inflammation, fibrosis, vascular and myocardial remodeling. 4,5 A paramagnetic effect can be observed by the iron deposits (e.g., intramyocardial hemorrhage of myocardial infarction, 6,7 iron overload of hemochromatosis and thalassemia, [8][9][10] and the net or relative increase of deoxygenated hemoglobin [compared with oxygenated hemoglobin] in the capillary blood, which ultimately shortens the T2* relaxation times, measured using BOLD (blood oxygen level dependent) MRI. 11,12 BOLD MRI can detect regional condition of myocardial oxygen supply and demand by means of paramagnetic properties.…”
mentioning
confidence: 99%